A Unified View on Varied Ultrafast Dynamics of the Primary Process in Microbial Rhodopsins. (29th November 2021) - Chang, Chun‐Fu; Kuramochi, Hikaru; Singh, Manish; Abe‐Yoshizumi, Rei; Tsukuda, Tatsuya; Kandori, Hideki; Tahara, Tahei
Abstract: All‐ trans to 13‐cis photoisomerization of the protonated retinal Schiff base (PRSB) chromophore is the primary step that triggers various biological functions of microbial rhodopsins. While this ultrafast primary process has been extensively studied, it has been recognized that the relevant excited‐state relaxation dynamics differ significantly from one rhodopsin to another. To elucidate the origin of the complicated ultrafast dynamics of the primary process in microbial rhodopsins, we studied the excited‐state dynamics of proteorhodopsin, its D97N mutant, and bacteriorhodopsin by femtosecond time‐resolved absorption (TA) spectroscopy in a wide pH range. The TA data showed that their excited‐state relaxation dynamics drastically change when pH approaches the p K a of the counterion residue of the PRSB chromophore in the ground state. This result reveals that the varied excited‐state relaxation dynamics in different rhodopsins mainly originate from the difference of the ground‐state heterogeneity (i.e., protonation/deprotonation of the PRSB counterion). Abstract : Varied excited‐state relaxation dynamics observed in the primary photoreaction of microbial rhodopsins are the ground‐state heterogeneity arising from the acid‐base equilibrium of the amino acid residue acting as the counterion of a protonated retinal Schiff base chromophore.